2007
DOI: 10.1002/ijc.22612
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new p16INK4A ELISA test and a high‐risk HPV DNA test for cervical cancer screening: Results from proof‐of‐concept study

Abstract: p16 INK4a , a cell cycle regulation protein, accumulates in abnormal epithelial cells infected with high-risk human papilloma virus (HPV). In immunostaining studies, p16 INK4a has shown potential as a marker of high grade cervical intraepithelial neoplasia (CIN) and invasive cervical cancer. To evaluate its potential use in cervical cancer screening, we conducted a feasibility study to compare the performance of a new enzyme linked immunosorbant assay (ELISA) for p16 INK4a (mtm laboratories, Heidelberg, Germa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…In the proof-of-principle study that we conducted among 319 women with abnormal cytology results, we found that, when the sample for p16 INK4a ELISA was collected before any other cervical sample, as was done in the present screening study, 90% of ≥CIN3, 77% with CIN2, and 53% with <CIN2 tested positive at the ≥8 pg/mL cut-point (21). In a similar proof-of-principle study conducted in Germany among women with abnormal screening cytology results, 97% of those with ≥CIN3, 96% with CIN2, and 55% with <CIN2 tested positive for p16 INK4a ELISA using the ≥8 pg/mL cut-point (22).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…In the proof-of-principle study that we conducted among 319 women with abnormal cytology results, we found that, when the sample for p16 INK4a ELISA was collected before any other cervical sample, as was done in the present screening study, 90% of ≥CIN3, 77% with CIN2, and 53% with <CIN2 tested positive at the ≥8 pg/mL cut-point (21). In a similar proof-of-principle study conducted in Germany among women with abnormal screening cytology results, 97% of those with ≥CIN3, 96% with CIN2, and 55% with <CIN2 tested positive for p16 INK4a ELISA using the ≥8 pg/mL cut-point (22).…”
Section: Discussionmentioning
confidence: 59%
“…The literature provides less consistent information on the influence of sampling order on performance of Pap and HPV tests. Previous work by our group (21) indicated that the p16…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…p16 cytology has been successfully used as a triage marker for ASCUS and LSIL cytology results [84,85] . Initial data on an ELISA-based p16 test suggest that it could be used as a simple test to evaluate the risk of cervical precancer [86,87] .…”
Section: P16mentioning
confidence: 99%
“…Two tested the performance of an ELISA for p16 INK4A (mtm laboratories, Heidelberg, Germany), the first being a proof-of-concept study with 319 cases [27], and the second a larger study [28] on 1,781 women by the same research group. This second study used an enhanced version of the p16 INK4A ELISA and showed promise in screening when combined with HC2, with comparable SE (91.8%) and higher SP (86.0%) compared to p16 INK4A ICC (table 1).…”
Section: What Are the Main Goals For Immunomarkers?mentioning
confidence: 99%